2017
DOI: 10.4236/ojmh.2017.74014
|View full text |Cite
|
Sign up to set email alerts
|

Weathering Processes on Martian Craters: Implications on Recurring Slope Lineae and the Location of Liquid Water

Abstract: Recent attention has been put into recurring slope lineae (RSL), after the discovery that water is present in them. It is assumed that RSL are due to flowing water. However, even though that might be the case, the general characteristics of RSL as well as their seasonal and spatial distribution in Mars, and their occurrence within craters, suggest that RSL correspond to the weathering of frozen aquifers, which coincides with slope stability processes occurring in impact craters and scree slopes from Earth. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This type of code can help to understand the formation of slope streaks, gullies, and recurring slope lineae. Garcia‐Chevesich et al () suggested that RSL are part of weathering processes, in which the constant freezing and thawing of water during Martian summer nights and days generate them. On the other hand, Núñez et al () argued that there is no clear indication of long‐lived liquid water to have a role in gully formation and evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of code can help to understand the formation of slope streaks, gullies, and recurring slope lineae. Garcia‐Chevesich et al () suggested that RSL are part of weathering processes, in which the constant freezing and thawing of water during Martian summer nights and days generate them. On the other hand, Núñez et al () argued that there is no clear indication of long‐lived liquid water to have a role in gully formation and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the geomorphological studies, together with an analysis of the energy budget of the area of interest, would take part in the strategic decision of future emplacement of human colonies. Not only is the energy issue of importance but also the geological and geomorphological aspects—for example, the presence of local water sources (Dundas et al, ), as well as the origin of recurring slope lineae (Garcia‐Chevesich et al, ).…”
Section: Introductionmentioning
confidence: 99%